Entertaining the Forgotten: Southern Governors and the Performance of Populism. Issue 1 (March 2021) - Twardowski, Weston; Fine, Gary Alan
Abstract : During the late 1920s and '30s, performative populism played a major role in the politics of the American Deep South. In the gubernatorial campaigns of three of the most prominent populist politicians of the era—Huey Long, Theodore Bilbo, and Eugene Talmadge—performance skills and entertainment were key strategies for gaining voter support and crafting personas within a popular imaginary.